The SAGE handbook of qualitative research in the Asian context - Wa-Mbaleka, Safary; Rosario, Arceli (London : SAGE Publications Ltd, 2022)
Qualitative research is growing in Asia and globally. In an Asian context, this requires an awareness of a completely different set of norms, practices, and expectations than those covered by books from a western perspective. This handbook truly celebrates these differences. Spanning the full research process, from philosophy and ethics to design and methods and through data collection, management, analysis, and dissemination, it focuses specifically on the practicalities needed to conduct effective and culturally responsive research in the Asian context. This handbook extends beyond researchers actually in Asia and also speaks to researchers working with Asian participants, researching in Asian immigrant neighbourhoods, and studying the larger global topics like socioeconomic challenges, climate change, or technological advancement. This is the first book to focus specifically on qualitative research in the Asian context and includes diverse contributors from Asia such as the Philippines, Singapore, Thailand, India, Oman, China, South Korea, Indonesia, Kazakhstan, Hong Kong, and from other continents such as North America, South America, Africa, Europe, and Oceania. Section 1: Foundations of Qualitative Research in Asia; Section 2: Qualitative Research Designs; Section 3: Best Practices in Dealing with Qualitative Research Data; and Section 4: Other Qualitative Research Topics.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Qualitative research -- Asia